High circulating activin A plasma levels are associated with tumour stage and poor survival in treatment-naive lung squamous cell cancer patients - Katharina Sinn; Ahmed Elbeialy; Berta Mosleh; Clemens Aigner; Karin Schelch; Viktoria Laszlo; Balazs Dome; Mir Alireza Hoda; Michael Grusch (Translational Oncology)
Objectives: Lung squamous cell carcinoma (LUSC) is associated with a poor prognosis and a lack of specific treatment options. The dysregulation of activin A (ActA) has been reported in various malignancies. Herein, we investigated the diagnostic and prognostic significance of ActA in LUSC. Materials and methods: ActA concentrations were measured using ELISA in plasma samples of 128 LUSC patients (stage I-IV) and 73 controls, and correlated those values with clinicopathological parameters and survival. Results: ActA plasma levels were significantly higher in therapy-naive LUSC patients compared to controls (444.1 ± 310.9 pg/mL vs 338.9 ± 145.5 pg/mL, p = 0.010). ActA levels significantly correlated with advanced stage as well as with T and N factors. High circulating ActA levels were significantly increased in metastatic disease patients compared to M0 disease. Further, patients with ActA levels above a computationally established optimal cut-off value of 443.0 pg/mL had a significantly worse median overall (OS, 17.63 vs 64.77 months, HR 0.391, 95 % CI 0.200–0.762, p < 0.001) and median disease-/progression-free survival (DFS/PFS; 11.57 vs 30.20 months, HR 0.502, 95 % CI 0.248–1.019, p = 0.020). Multivariate analysis revealed that high ActA levels were an independent prognostic factor for shorter OS (p = 0.001) and DFS/PFS (p = 0.018). A newly developed score combining CRP and ActA levels was also an independent prognostic factor for OS and DFS/PFS. Conclusion: Measurement of circulating ActA levels may help identify advanced-stage LUSC patients, and this value could serve as a prognostic parameter in LUSC. Thus, ActA may be a novel blood-based biomarker for identifying LUSC patients with distant metastasis.